Effect Annealing Temperatures On The Structural Proerties of ZnO Thin Films Prepared By Chemical Bath Deposition - Shehab, A. A.; Salman, S. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research, we study the changing structural properties of ZnO with changing annealing temp., in the range  (473-773)K prepared by chemical bath deposition method at temp. (353)K, where deposited on glasses substrates at thickness (500Â±25)nm, the investigation of (XRD) indicates that the (ZnO) films are polycrystalline type of Hexagonal.            The results of the measuring of each sample from grain size, microstrain, dislocation density, integral breadth, shape factor and texture coefficient, show that annealing process leads to increase the grain size (26.74-57.96)nm, and decrease microstrain (0.130-0.01478), dislocation density (1.398-0.297)*1015 and increase texture coefficient.